Haunted Encounters: Exile and Holocaust Literature in German and Austrian Post-war Culture - Lang, Birgit (Religions (Basel, Switzerland ), 2012)
In an essay titled ‘The Exiled Tongue’ (2002), Nobel Prize winner Imre Kertész develops a genealogy of Holocaust and émigré writing, in which the German language plays an important, albeit contradictory, role. While the German language signified intellectual independence and freedom of self-definition (against one’s roots) for Kertész before the Holocaust, he notes (based on his engagement with fellow writer Jean Améry) that writing in German created severe difficulties in the post-war era. Using the examples of Hilde Spiel and Friedrich Torberg, this article explores this notion and asks how the loss of language experienced by Holocaust survivors impacted on these two Austrian-Jewish writers. The article argues that, while the works of Spiel and Torberg are haunted by the Shoah, the two writers do not write in the post-Auschwitz language that Kertész delineates in his essays, but are instead shaped by the exile experience of both writers. At the same time though, Kertész’ concept seems to be haunted by exile, as his reception of Jean Améry’s works, which form the basis of his linguistic genealogies, shows an inability to integrate the experience of exile.